Wound care and the NHS 10-year health plan: aligning clinical innovation with system value - Richard H Shorney; James Saunders (British Journal of Community Nursing, 2026)
The NHS Fit for the Future 10 Year Health Plan published in July 2025, represents the most ambitious structural redesign of the health service for a generation. For wound care, this creates both significant challenges and considerable opportunities. This article examines how wound care products and services can be aligned with the strategic priorities of the 10-year plan, including three systemic shifts, in addition to value-based procurement reform and drug tariff changes. These changes will affect how wound care products already listed on drug tariff are assessed through a renewal process. This is a narrative review of policy documentation, including the 10-year health plan, NHS England procurement guidance and value-based procurement frameworks, supplemented by analysis of pilot programmes and regional exemplars. Wound care is uniquely positioned to demonstrate value across all three of the plan's strategic shifts: from hospital to community, from analogue to digital and from sickness to prevention. Value-based procurement and drug tariff reform offer practical mechanisms for realigning wound care commissioning with system outcomes. Wound care should be repositioned not as a clinical commodity but as a strategic system resource. Organisations and industry partners that can evidence system value, not just clinical efficacy, are best placed to benefit from this NHS transformation.